Potential for Exporting Vietnamese Fish Sauce (International Journal of Scientific Research and Management (IJSRM), 2024)
A culture’s identity and spirit are both embodied in its fish sauce. Fish sauce is often seen by visitors as a distinctive feature of Vietnam. When it comes to their native food, Vietnamese people take great pleasure in their fish sauce, which they use in all of their meals as the "National Soul" flavor. This article will look into Vietnamese fish sauce exports as of right now, as well as market trends, the product’s export orientation, the pros and disadvantages of Vietnamese fish sauce goods, and possibilities and problems in exporting fish sauce products to other countries. As a sample case study of Vietnamese fish sauce, Phu Quoc fish sauce is mentioned in the article. The research team uses the findings as a foundation to think through and suggest ways to increase the effectiveness of Vietnamese fish sauce exports.